2022
DOI: 10.1172/jci160152
|View full text |Cite
|
Sign up to set email alerts
|

Targeting acetylcholine signaling modulates persistent drug tolerance in EGFR-mutant lung cancer and impedes tumor relapse

Abstract: Although first-line epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) therapy is effective for treating EGFR-mutant non-small cell lung cancer (NSCLC), it is now understood that drug-tolerant persister (DTP) cells escaping from initial treatment eventually drives drug resistance. Here, through integration of metabolomics and transcriptomics, we found that the neurotransmitter acetylcholine (ACh) was specifically accumulated in DTP cells, and illustrated that treatment with EGFR-TKI height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 87 publications
0
19
0
Order By: Relevance
“…J. Wu et al observed that M3 levels were elevated in metaplasia/dysplastic tissues compared to the matched normal tissues, and M3R expression was increased in Stage II and III NSCLC relative to Stage I NSCLC [ 112 ]. Recently, Meng Nie et al demonstrated that upregulated ACh metabolism mediated drug tolerance in drug-tolerant persister (DTP) cells partly through the activation of WNT signaling in an ACh/M3-dependent manner [ 113 ]. In addition, targeting acetylcholine signaling modulates persistent drug resistance in epidermal growth factor receptor (EGFR)-mutant lung cancer and prevents tumor recurrence [ 113 ].…”
Section: Acetylcholine System In Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…J. Wu et al observed that M3 levels were elevated in metaplasia/dysplastic tissues compared to the matched normal tissues, and M3R expression was increased in Stage II and III NSCLC relative to Stage I NSCLC [ 112 ]. Recently, Meng Nie et al demonstrated that upregulated ACh metabolism mediated drug tolerance in drug-tolerant persister (DTP) cells partly through the activation of WNT signaling in an ACh/M3-dependent manner [ 113 ]. In addition, targeting acetylcholine signaling modulates persistent drug resistance in epidermal growth factor receptor (EGFR)-mutant lung cancer and prevents tumor recurrence [ 113 ].…”
Section: Acetylcholine System In Lung Cancermentioning
confidence: 99%
“…Recently, Meng Nie et al demonstrated that upregulated ACh metabolism mediated drug tolerance in drug-tolerant persister (DTP) cells partly through the activation of WNT signaling in an ACh/M3-dependent manner [ 113 ]. In addition, targeting acetylcholine signaling modulates persistent drug resistance in epidermal growth factor receptor (EGFR)-mutant lung cancer and prevents tumor recurrence [ 113 ]. On the other hand, M2 signaling also possesses the potential to promote tumor growth and accelerate EMT in NSCLC [ 107 ].…”
Section: Acetylcholine System In Lung Cancermentioning
confidence: 99%
“…In addition to the identification of initial treatment options, patientderived models can also help in revealing the resistance mechanisms (Nie et al, 2022) and PDX models captured at the moment of maximal tumor shrinkage during exposure to antitumor agents provided a valuable opportunity for exploring the possible resistance mechanisms before real resistance occurs (Lupo et al, 2020). Singlecell sequencing on the residual PDX models has demonstrated its potential to reveal the evolutionary and selective mechanisms under the selection pressure of anti-cancer drugs (Rambow et al, 2018).…”
Section: Approaching Personalized Precision Medicinementioning
confidence: 99%
“…10 It also reveals an unprecedented mechanism by which RNA structural switches regulate EGFR-TKI resistance by controlling the yrdC N6-threonylcarbamoyltransferase domain containing (YRDC) mRNA translation in an embryonic lethal abnormal vision-like 1 (ELAVL1) -dependent manner. 11 Recent work by Nie et al 12 revealed that EGFR-TKI treatment in NSCLC leads to metabolic remodeling of the neurotransmitter acetylcholine (ACh) in cells with drug-tolerant persister (DTP) and its regulatory mechanism. Zhang et al 13 screened the protein molecule AKR1B1 associated with drug resistance in the in vitro and in vivo drug resistance model in line with the clinical treatment pathway and the clinical drug resistance recurrence database based on the results of previous studies, combined with transcriptomic analysis, and functional studies found that the survival, growth, and drug resistance of a variety of tumor cell models resistant to first-and third-generation EGFR-TKIs were dependent on AKR1B1.…”
Section: Drug Resistance Dilemmas Of Targeted Therapy and Coping Stra...mentioning
confidence: 99%